Tren Motivasi Pada Komunitas Pelari: Apakah Kesehatan Mental Lebih Dominan Daripada Kesehatan Fisik? - Sugiati, Sugiati; Afiah, Nur (Universitas PGRI Kanjuruhan Malang, 2025)
The increasing participation in running communities has been driven by the growing awareness of the benefits of exercise for both physical and mental health. This study aims to analyze the dominant factor motivating individuals in running communities—whether mental health or physical health plays a more significant role. This research employs a quantitative approach with an explanatory design, involving 65 respondents from running communities in Parepare City, selected through purposive sampling. Data were collected using a structured questionnaire measuring physical health, mental health, and sports participation motivation, with multiple linear regression as the primary data analysis technique. The findings indicate that mental health has a more significant impact on individuals’ motivation to participate in running communities compared to physical health. Regression analysis reveals that mental health positively influences sports participation motivation, whereas physical health does not show a significant effect. These findings suggest that psychological factors, such as emotional well-being and stress-coping mechanisms, play a crucial role in sustaining engagement in running communities rather than physical benefits alone. The implications of this study emphasize the importance of sports-based interventions focusing on mental well-being to enhance long-term participation in physical activities.